Modeling and Risk Assessment of Man-Made Disasters at Petrochemical Enterprises - Sukach, S.; Cheberiachko, Yu.; Petrenko, I.; Rieznik, D.; Hubachov, O.; Tsybulnyk, N. (Science and Innovation, 2023)
Introduction. Emergency modeling technologies have been increasingly used to prevent man-made disasters. At the same time, in order to expand (clarify) the obtained results, additional risks need to be assessed. Problem Statement. The issue of safety in the production and storage of petroleum products is very important, because there is a high risk of toxic emissions, fires, and explosions, which may lead to catastrophic situations with casualties. Purpose. The purpose of this research is to model possible scenarios and to assess the risks of emergencies at oil production and storage facilities. Material and Methods. Based on the analysis of literature sources on this and related topics, we have used the empirical method consisting of mathematical calculations and computer simulations with the use of software. Results. Three computer simulations of emergencies at a refinery, which may occur under different circumstances, have been made. With the help of these simulations, possible consequences of the emergency have been obtained. The probable risks of human exposure to heat radiation have also been assessed. With the use of probit functions, the dependencies of the conditional probability of exceeding the pain threshold, as well as 1st, 2nd, and 3rd degree burns have been determined. This has allowed improving and balancing the management decision-making system regarding the implementation of emergency response measures. Recommendations have been given for controlling zones and reducing the potential risk of emergency situations on petrochemical enterprises (factories). Conclusions. The obtained results can be used to modernize the existing system of continuous observations, laboratory and other control, to assess the status of protection of the population, territories, and objects under increased risk of danger, as well as to rationalize the system of medical and evacuation support. The obtained cartographic materials can be used for training officers and employees of the State Emergency Service of Ukraine.